Use of seaweed-based biostimulant (Ascophyllum nodosum) on ornamental sunflower seed germination and seedling growth - Ferreira dos Santos, Patrick Luan [UNESP]; Zabotto, Alessandro Reinaldo [UNESP]; Correa Jordao, Half Weinberg [UNESP]; Villas Boas, Roberto Lyra [UNESP]; Broetto, Fernando [UNESP]; Tavares, Armando Reis (Soc Brasileira Floricultura & Plantas Ornamentais, 2019)
Seaweed extracts are employed as biostimulants due to their beneficial effects on crop growth and yield. Ascophyllum nodosum seaweed extract aid to improve seedling growth and development, and decrease seedlings production costs; however, the correct concentration must be used in order to maximize the biostimulant effects. Consequently, this study aimed to analyze the effects of different concentrations of a seaweed-based (Ascophyllum nodosum) biostimulant on ornamental sunflower seed germination and seedling growth. Seeds of ornamental sunflower cv. Sol Pleno were sown in polyethylene trays containing commercial substrate. The treatments consisted of dairy spraying 60 mL of the solutions 0 (control), 5, 10 or 15 mL L-1 biostimulant on substrate. The experimental design was completely randomized with 4 treatments (concentrations of biostimulant) and 4 replicates (10 seeds replicate(-1)). The evaluated variables were percentage, index and time averages of germination, seedling height, fresh and dry mass of shoot and roots, and root system morphology (WinRhizo). The increase of the biostimulant concentration enhances seed germination and seedlings development. The concentration 15 mL L-1 biostimulant showed the best results for percentage and index of germination and the lowest mean germination time and increase plant height and fresh and dry mass of shoots in relation to the control treatment. Accordingly, 15 mL L-1 biostimulant (Ascophyllum nodosum) is recommended for ornamental sunflower Sol Pleno seed germination and seedlings growth.
Keywords: Helianthus annuus; seedling production; seaweed extract; seed germination